Domestic and International Mainstream BIM Software Application and Comparison Study. Issue 1 (1st January 2022) - Wang, Ying; Zhu, Jiwei; Wei, Baojun
Abstract: With the rapid development of science and technology, the construction industry is showing the trend of informatization. BIM has emerged to bring vitality into the construction industry. This paper introduces the application of BIM software in various phases and the mainstream BIM software at home and abroad, and conducts a comparative study on each BIM software from the design phase, construction phase and operation and maintenance phase, analyses the advantages and disadvantages of each software, and helps relevant practitioners to quickly choose the appropriate software according to their needs.